2019
DOI: 10.1108/jsm-10-2018-0288
|View full text |Cite
|
Sign up to set email alerts
|

Customer participation and service outcomes: mediating role of task-related affective well-being

Abstract: Purpose-This paper contributes to transformative service research by drawing on selfdetermination, elicitation of emotions framework, and feelings-as-information theories to explore how customer participation, task-related affective well-being, customer knowledge, task complexity, and service outcomes relate with each other. Design/methodology/approach-A synthesis of relevant literature on customer participation and customer well-being reveals a conceptual model with eleven testable propositions. Findings-The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 84 publications
(106 reference statements)
1
13
0
Order By: Relevance
“…In line with the recent plea to consider customer well-being as a managerially relevant outcome in financial services (Asokan Ajitha et al , 2019), the findings also provide actionable managerial implications for changing customers’ perspectives regarding their relationships with the Romanian banking system. Specifically, the banks seek to increase trust and to move the focus from merely improving their financial behaviors to enhancing customers’ FWB.…”
Section: Managerial Implicationssupporting
confidence: 71%
See 1 more Smart Citation
“…In line with the recent plea to consider customer well-being as a managerially relevant outcome in financial services (Asokan Ajitha et al , 2019), the findings also provide actionable managerial implications for changing customers’ perspectives regarding their relationships with the Romanian banking system. Specifically, the banks seek to increase trust and to move the focus from merely improving their financial behaviors to enhancing customers’ FWB.…”
Section: Managerial Implicationssupporting
confidence: 71%
“…The results illustrate that, at this point, there is an existing opportunity or niche in the Romanian market for financial advisors if they can position themselves as mediators between banks and individuals. That is, if they address the trust aspects properly concerning customer participation, better service outcomes and a higher level of well-being (Asokan Ajitha et al , 2019) may result. This is also supported by recent results illustrating that the advice dimension of collectivism, as measured for Romanians with the Auckland Individualism and Collectivism Scale, significantly impacts the subjective norms regarding the adoption of sharing economy services (Ianole-Călin et al , 2020), a sector characterized by many transformative attributes.…”
Section: Managerial Implicationsmentioning
confidence: 99%
“…However, most of the research into employee innovation behavior has been conducted in manufacturing industries rather than in a service sector context (Li and Hsu, 2016a;Nazir et al, 2018). Innovation behavior in the service sector, by its nature, relies on service encounters-especially interactions between frontline employees and customers (Kelley et al, 1990;Ajitha et al, 2019). More recently, researchers have focused on open service innovation logic, which views customers as external resource providers during the innovation process (Mina et al, 2014;Wang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that customers' affective experience of a brand influences their feeling of prestige toward the brand (Choi et al, 2017); such prestige also reflects their status to other people during the experience (Hayakawa et al, 2018). The affective experience of a customer has also been found to exert a positive influence on their hedonic well-being in integrated resorts and cultural heritage destinations (sharmiladevi & Rameshraj, 2017), and when customers cocreate the experience (Ajitha et al, 2019). H 3a : The affective experience of passengers in a first-class cabin significantly influences them to feel prestigious.…”
Section: Experience Effects On the Duality Of Luxurymentioning
confidence: 99%